2005
DOI: 10.1196/annals.1282.045
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Used by Relaxin to Regulate Myometrial Phospholipase C

Abstract: Relaxin exhibits pleiotropic effects on reproductive and nonreproductive tissues; the signaling mechanisms underlying these functions are still not well understood. Activation of protein kinase A and several other signal-regulated protein kinases results in the phosphorylation of phospholipase C (PLC)-beta3 and inhibit Galpha(q)-stimulated PLC activity. Therefore, PLCbeta3 may be targeted by both contractant and relaxant signaling pathways in myometrium and play a critical role in the balance between them. PHM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Hyperactivation of the PI3K/AKT pathway leads to promotion of cell survival and inhibition of apoptosis. However, previous studies showed that relaxin was unable to activate AKT in normal endometrial cells (29,30) or human acute monocytic leukemia cell line (THP-1) (29,31). In the present study we did not observe the phosphorylation of AKT by treatment with rH2 relaxin in cultured uterine leiomyoma cells (data not shown).…”
Section: Discussioncontrasting
confidence: 81%
“…Hyperactivation of the PI3K/AKT pathway leads to promotion of cell survival and inhibition of apoptosis. However, previous studies showed that relaxin was unable to activate AKT in normal endometrial cells (29,30) or human acute monocytic leukemia cell line (THP-1) (29,31). In the present study we did not observe the phosphorylation of AKT by treatment with rH2 relaxin in cultured uterine leiomyoma cells (data not shown).…”
Section: Discussioncontrasting
confidence: 81%
“…PLCB1 is not a substrate of PRKA, and may account for the PRKA-resistant PLC component of the activity elicited by OXT. PLCB4 has not been shown to be a target of PRKA or PRKC, and lacks a potential target sequence in the homologous region [11]. Although there is some evidence that receptors coupling to Ga q can preferentially couple to a given PLCB subtype [44][45][46], there is no evidence to date that OXTR exhibits this ability.…”
Section: Plcb3 Phosphorylation In Human Myometrial Cellsmentioning
confidence: 97%
“…PRKA phosphorylates PLCB3 exclusively on Serine 1105 (S 1105 ) and inhibits both Ga q -and Gbc-stimulated activity in transfected cells [8,10]. S 1105 is conserved between a number of species in a reasonable consensus PRKA target sequence in PLCB3, but a comparable sequence is not present in the other PLCB isoforms [11]. Interestingly, PLCB3-S 1105 is also phosphorylated by activation of PRKC and protein kinase G [10,12].…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, the amount of PLCB4 is increased at midpregnancy, whereas PLCB1, PLCB2, and PLCB3 are up-regulated at term in the rat uterus (Mhaouty-Kodja et al 2004). PLCB3 may be targeted by both contractant and relaxant signaling pathways in the human myometrium and play a critical role in the balance between them (Zhong et al 2005). Both DAG-sensitive PKC, activated by PLCB products, and diacylglycerol (DAG)-insensitive PKC, possibly activated by PI3K-dependent process are involved in ERK activation to modulate rat uterine functions (Robin et al 2002).…”
Section: Phosphatidyl Inositol Signaling Pathwaymentioning
confidence: 99%